Podmiotowość prawna gminy - Szewczyk, Marek (Wydział Prawa i Administracji UAM, 1993)
The author analyses the problem of legal personality of a commune (gmina) on the grounds of some basic theoretical conceptions concerning the nature of territorial government as well as in the context of new regulations adopted in the Republic of Poland.
Legal personality of commune